2021
DOI: 10.1093/ofid/ofab015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Longevity of SARS-CoV-2 Antibodies Among Health Care Workers

Abstract: Background Understanding SARS-CoV-2 antibody prevalence in a spectrum of healthcare workers (HCWs) may provide benchmarks of susceptibility, help understand risk stratification, and support enactment of better health policies and procedures. Method Blood serum was sampled at enrollment and 8-week follow-up from HCWs (n=3,458) and from community first responders (n=226) for IgG analyses. Demographics, job duties, location, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Our previous HCW sero-suvaillance studies have shown a low prevalence of antibodies ranging from 0.98% to 2.58% depending on sampling timing (e.g., before or after partial state re-opening in late May, 2020) [5,6]. Serology prevalence in HCWs was found to be loosely correlated with community prevalence [6].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Our previous HCW sero-suvaillance studies have shown a low prevalence of antibodies ranging from 0.98% to 2.58% depending on sampling timing (e.g., before or after partial state re-opening in late May, 2020) [5,6]. Serology prevalence in HCWs was found to be loosely correlated with community prevalence [6].…”
Section: Introductionmentioning
confidence: 83%
“…Prior sero-suvaillance studies among HCWs have reported widely ranging antibody prevalence from 89.3% in Wuhan, China (n=424) [1], 35.8% in New York City (n=285) [2], to 7.4% in Milan, Italy [3], and 2.67% in Denmark (n=28,792) [4]. Our previous HCW sero-suvaillance studies have shown a low prevalence of antibodies ranging from 0.98% to 2.58% depending on sampling timing (e.g., before or after partial state re-opening in late May, 2020) [5,6]. Serology prevalence in HCWs was found to be loosely correlated with community prevalence [6].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…A similar spillover effect has been hypothesized for low HCW seroprevalence relative to the surrounding community in California. 2 In complement, researchers at a large New York City (NYC) hospital found higher overall HCW seropositivity rates compared with the community, though estimates were strikingly variable after detailed stratification by job function and location. 3 The gradient of seroprevalence showed the highest risk among nurses and those in nonclinical, low-wage jobs (eg, patient transport, housekeeping), a finding also seen in another US study prior to adjustment for demographic and community factors.…”
mentioning
confidence: 99%
“…6 Several studies comparing HCW to local community seropositivity rates have reached disparate conclusions. 2,7 These contrasting data may result from variability in vigilance of PPE use, mask use in work rooms or during meals/breaktimes, sick leave policies driven by staffing demands, and neighborhood factors. In addition, selection biases and timing of blood sampling relative to viral transmission peaks (with differing degrees of temporal antibody waning) may contribute to the apparent discordance.…”
mentioning
confidence: 99%